Naar een nieuwe schoolstrijd? - Sunier, T. (BMGN - Low Countries Historical Review, 2004)
The school funding controversy revisited Since the mid 1970s, there has been an ongoing debate in the Netherlands about Islam’s place in society. When following this debate, one might easily get the impression that we are dealing with a completely new and unprecedented phenomenon. A more thorough analysis, however, shows that this is only partly the case. When we put the debate about Islam into a historical perspective, focussing on the relationship between state and religion, the way in which Dutch society has dealt with issues of religious diversity, and how religious newcomers have been treated in the past, we are able to see that there are remarkable parallels with previous cases of religious emancipation and integration. In this article, the current debate about education and Islamic schools will be compared with aspects of the so-called school funding controversy that took place around the beginning of the 20th century. This article is part of the special issue ’Godsdienst in Nederland’.